The Influence of Participative Leadership, Organizational Commitment, Organizational Culture on the Retention Interest of Private High School Teachers in Sidoarjo District - Nela Budi Astuti; Syunu Trihantoyo; Ayu Wulandari; Amrozi Khamidi (CV. Edujavare Publishing, 2026)
This study examines the influence of participative leadership, organizational commitment, and organizational culture on teacher retention intention in private senior high schools in Sidoarjo District. The novelty of this research lies in the integrated analysis of these three organizational factors within the context of private secondary education, where empirical studies remain limited. A quantitative approach with a causal associative design was employed involving 169 teachers from six private senior high schools selected through total sampling. Data were collected using questionnaires and analyzed through descriptive statistics, Pearson correlation, multiple linear regression, and bootstrap-based hypothesis testing. The results indicate that participative leadership (p = 0.012), organizational commitment (p = 0.001), and organizational culture (p = 0.008) each have a positive and significant effect on teacher retention intention. Simultaneously, the three variables significantly influence teacher retention intention, explaining 73.8% of its variance. These findings highlight the importance of leadership and organizational factors in strengthening teacher retention in private schools.